2016
DOI: 10.1016/bs.irrdd.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep in Neurodevelopmental Disorders

Abstract: Individuals with intellectual and developmental disabilities (IDD) experience sleep problems at higher rates than the general population. Although individuals with IDD are a heterogeneous group, several sleep problems cluster within genetic syndromes or disorders. This review summarizes the prevalence of sleep problems experienced by individuals with Angelman syndrome, Cornelia de Lange syndrome, Cri du Chat syndrome, Down syndrome, fragile X syndrome, Prader-Willi syndrome, Smith-Magenis syndrome, Williams sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 182 publications
(275 reference statements)
2
33
0
1
Order By: Relevance
“…GO analysis of all 833 DEGs in the mutant hypothalamus following SD suggested, instead, that loss of Snord116 leads to a homeostatic response that relies on several cellular growth processes of the hypothalamus ( Figure 3E). This result indicates that defects in sleep homeostasis in PWS can be derived from development processes of the hypothalamus, as has been described in other neurodevelopmental disorders [57][58][59].…”
Section: Discussionsupporting
confidence: 68%
“…GO analysis of all 833 DEGs in the mutant hypothalamus following SD suggested, instead, that loss of Snord116 leads to a homeostatic response that relies on several cellular growth processes of the hypothalamus ( Figure 3E). This result indicates that defects in sleep homeostasis in PWS can be derived from development processes of the hypothalamus, as has been described in other neurodevelopmental disorders [57][58][59].…”
Section: Discussionsupporting
confidence: 68%
“…Studies of shift work have demonstrated that sleep deprivation (SD) results in the epigenetic and transcriptional dysregulation of core circadian genes and increased risk for adverse metabolic phenotypes and cancer 13,14 . The epigenetic and metabolic dysregulation associated with SD in healthy individuals provides a basis for understanding these characteristics in the context of neurodevelopmental disorders, which often share a core sleep phenotype among their unique distinguishing features 15 .…”
mentioning
confidence: 99%
“…Children with DS frequently experience poor, shorter and disrupted sleep (Esbensen & Schwichtenberg ). This study contributes to our understanding of the practical impact of sleep on the executive functioning of school‐age children with DS, particularly inhibitory control.…”
Section: Discussionmentioning
confidence: 99%